Blockchain Integration in Salesforce CRM: A Framework for Enhanced Supply Chain Traceability and Stakeholder Trust - Sruthi Potru, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the integration of blockchain technology with Salesforce CRM for enhanced supply chain management and traceability. The article investigates how decentralized ledger technology creates a transparent, immutable record-keeping system that enables real-time tracking of products throughout their lifecycle. Through analysis of implementation frameworks and stakeholder interactions, this article demonstrates how blockchain-enhanced CRM systems provide a single source of truth, improving visibility and accountability across the supply chain network. The article reveals that this integration offers significant advantages in fraud prevention, dispute resolution, and quality assurance while strengthening relationships between supply chain partners. The article also explores how the combination of blockchain and Salesforce CRM facilitates more informed decision-making through accurate, real-time data access and analysis. Furthermore, the article highlights the system's role in streamlining operations, reducing errors, and enhancing customer satisfaction through improved product authenticity verification and traceability. This article contributes to the growing body of knowledge on digital transformation in supply chain management and provides practical insights for organizations seeking to implement blockchain-enhanced CRM solutions.
Keywords: Blockchain Integration; Supply Chain Traceability; Salesforce CRM; Digital Supply Chain Management; Enterprise Decentralization